The metatranscriptome of resident microbiota in the gut of blue mussels, Mytilus edulis, under standard laboratory conditions - Tyler W. Griffin; Lisa M. Nigro; Hannah I. Collins; Bridget A. Holohan; J. Evan Ward (Current Research in Biotechnology, 2024)
Metatranscriptomic methods involving RNA sequencing (RNA-seq) are powerful tools for evaluating the gene expression profiles of transcriptionally-active microbes that inhabit the tissues of animals. Bivalve molluscs, like all invertebrates, are holobionts and sites of interactions between host animals and both prokaryotic and eukaryotic symbionts. The present communication describes the metatranscriptomic profile of the resident microorganisms that inhabit the gut of blue mussels, Mytilus edulis, under standard laboratory conditions. Each of the eight mussels described herein were housed in isolated microcosms with routine husbandry for 14 days before their gut tissues were sampled and subjected to RNA-seq. Subsequent mRNA reads that aligned to the mussel genome were removed, and the non-host reads were annotated for function and pathway analyses. Under laboratory conditions, the resident gut microbiota expressed genes associated mostly with aerobic energy processes, with other notable contributions from metabolism and protein processing genes. At the pathway level, the most abundant complete pathways expressed in the resident gut microbial communities were related to aerobic cellular respiration, nucleotide biosynthesis, and catabolism. These data represent novel, baseline microbial gene expression information from the gut of mussels, which are crucial for future research examining the mussel holobiont and bivalve microbial ecology. Public retrieval and secondary analyses of these metatranscriptomic profiles are highly encouraged.